Assessing patient‐reported symptom burden of long‐term head and neck cancer survivors at annual surveillance in survivorship clinic. Issue 8 (29th February 2020) - Townes, Thomas G.; Navuluri, Sriram; Pytynia, Kristen B.; Gunn, Gary Brandon; Kamal, Mona J.; Gilmore, Katherine R.; Chapman, Patricia H.; Bell, Katherine V.; Fournier, Danielle M.; Janik, Monica A.; Joseph, Liza M.; Zendehdel, Sara; et al.
Abstract: Background: This study reports long‐term head and neck cancer (HNC) patient‐reported symptoms using the MD Anderson Symptom Inventory Head and Neck Cancer Module (MDASI‐HN) in a large cohort of HNC survivors. Methods: MDASI‐HN results were prospectively collected from an institutional survivorship database. Associations with clinicopathologic data were analyzed using χ 2, Mann‐Whitney, and univariate regression. Results: Nine hundred and twenty‐eight patients were included. Forty‐six percent had oropharyngeal primary tumors. Eighty‐two percent had squamous cell carcinoma. Fifty‐six percent of patients had ablative surgery and 81% had radiation therapy as a component of treatment. The most severe symptoms were xerostomia and dysphagia. Symptom scores were worst for hypopharynx and varied by subsite. Patients treated with chemoradiation or surgery followed by radiation ± chemotherapy reported the worst symptoms while patient treated with surgery plus radiation ± chemotherapy reported the worst interference. Conclusion: HNC survivors describe their long‐term symptom burden and inform efforts to improve care many years into survivorship.